Separability and public finance - Stéphane Gauthier; Guy Laroque (Institute for Fiscal Studies (IFS), 2008)
In a second best environment, the optimal policy choice sometimes follows the first best rules. This note lays down the information structure and separability assumptions under which this property holds in a variety of setups.
Keywords: H21; H11; 330; separability; second best optimality; indirect taxes; Samuelson rule; Pigovian taxation; Öffentliche Finanzwirtschaft; Einkommensumverteilung; Indirekte Steuer; Kopfsteuer; Vollkommene Information; Theorie